2019
DOI: 10.1177/2043808719875274
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive bias modification for interpretation training via smartphones for social anxiety in Chinese undergraduates

Abstract: To address the unmet need for treatment of social anxiety disorder in China, it is timely and relevant to identify more effective, accessible, economic, and easily disseminated interventions. The present study examined the effect of an eight-session program for cognitive bias modification for interpretation (CBM-I). Smartphones were used in the training of reducing interpretation bias and social anxiety of Chinese undergraduates with high social anxiety. In total, 38 participants were randomly assigned to eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Two studies tested smartphone app-based cognitive bias modification programme in people with social anxiety. One RCT study (Sun et al, 2019 ) showed that the level of social anxiety significantly reduced in the intervention group compared to that in the control group post-treatment and sustained at 1-month follow-up. Another RCT study (Yang et al, 2017 ) compared three different forms of cognitive bias modification programmes (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies tested smartphone app-based cognitive bias modification programme in people with social anxiety. One RCT study (Sun et al, 2019 ) showed that the level of social anxiety significantly reduced in the intervention group compared to that in the control group post-treatment and sustained at 1-month follow-up. Another RCT study (Yang et al, 2017 ) compared three different forms of cognitive bias modification programmes (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies evaluated the acceptability and feasibility of two smartphone app-based interventions: one study on a smartphone app for perinatal depression and the other four studies about an app for SUD. One RCT (Sun et al, 2021) reported poor intervention completion rates for an app-based mindfulness training on perinatal depression; 52.3% of participants in the intervention group completed at least 4 weeks of the intervention and only 8% completed the full 8-week intervention programme. For smartphone apps for SUD, participants from one RCT study (Liang, Han, Du, Zhao, & Hser, 2018a) reported that the content was easy to understand in only 55% of cases, although 72% said that the app was easy to use.…”
Section: Smartphone Appsmentioning
confidence: 99%
“…Beard and Amir [21] asked socially anxious individuals to complete eight rounds of IMP training, thereby demonstrating that changes to benign interpretation biases could mediate the modification's effects on anxiety. By contrast, Sun, Yang, Zhang, Xiao and Cui [18] reported that an altered interpretation bias did not mediate anxiety changes. One possible explanation for these inconsistent results is that interpretation biases were measured differently between studies, which may imply that the central issue for improving IBM's effectiveness is using more specific measures for interpretation biases and testing their influences on anxiety.…”
Section: Introductionmentioning
confidence: 84%
“…Despite this potential, no previous studies have used mobile devices to promote IBM for reducing anxiety [16,17]. It is also worth noting that only two studies even examined the feasibility of smartphone-based IBM [16,18]. In both cases, participants accessed IBM training through website links they received on their mobile phones, with no differences to previous, laboratory-based or online training studies; moreover, each study implemented homogenous training and assessment tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of social anxiety among college students is about 7-33% (Honnekeri et al, 2017;Jaiswal et al, 2020), and social anxiety is as prevalent among college students in the United States as it is in the general population (Schry et al, 2012). Likewise, in China, social anxiety is one of the serious public health problems in the college student population (Sun et al, 2019;Xia et al, 2023). If social anxiety is not ameliorated or corrected, it may develop into severe social anxiety disorder (SAD) and negatively affect college students' academic performance, academic achievement and social relationships (Brook and Willoughby, 2015).…”
Section: Introductionmentioning
confidence: 99%